A Study on the Motivation of Post-90s Financial Industry Employees in China - Ma, Yongxin (2022)
Effective talent management is critical to the organization's success, and employee motivation is an essential function of human resource management. As post-90s employees become the primary labor force of companies, it is crucial to study this topic. This research aims to recognize the factors that might influence the work motivation of Chinese post-90s employees in the financial industry. The study identified five motivating factors: company policies, salary, work conditions, relationships, and supervision. This study used a quantitative research method and collected 255 questionnaires as part of it. Descriptive analysis, correlation analysis, and regression analysis were performed on the data by using SPSS software. The results showed that all five factors had significant positive impacts on employee motivation. The study concluded with several recommendations to facilitate future research in this area and help companies improve their human resources management.